Effectiveness of neuromuscular taping on pronated foot posture and walking plantar pressures in amateur runners. Issue 4 (April 2016) - Aguilar, María Bravo; Abián-Vicén, Javier; Halstead, Jill; Gijon-Nogueron, Gabriel
Abstract: Objectives: To determine the effect kinesiotaping (KT) versus sham kinesiotaping (sham KT) in the repositioning of pronated feet after a short running. Design: Prospective, randomised, double-blinded, using a repeated-measures design with no cross-over. Methods: 116 amateur runners were screened by assessing the post-run (45 min duration) foot posture to identify pronated foot types (defined by Foot Posture Index [FPI] score of ≥6). Seventy-three runners met the inclusion criteria and were allocated into two treatment groups, KT ( n = 49) and sham KT ( n = 24). After applying either the KT or sham KT and completing 45 min of running (mean speed of 12 km/h), outcome measures were collected (FPI and walking Pedobarography). Results: FPI was reduced in both groups, more so in the KT group (mean FPI between group difference = 0.9, CI 0.1–1.9), with a score closer to neutral. There were statistically significant differences between KT and sham KT ( p < .05 and p < .01) in pressure time integral, suggesting that sham KT had a greater effect. Conclusions: KT may be of some assistant to clinicians in correction of pronated foot posture in a short-term. There was no effect of KT, however on pressure variables at heel strike or toe-off following a short duration of running, the sham KT technique had a greater effect. Level of evidence: Therapy, level 1b.